Scientific Skills Through Guided Inquiry: A Case Study of Briquette Production from Corncob and Coffee Grounds - Widiastuti, Egita; Windayani, Neneng; Sukmawardani, Yulia; Rahmawati, Risa (Universitas Pendidikan Mandalika, 2025)
This study aims to develop students' scientific performance with the help of guided inquiry-based learner worksheets (LKPD) in developing students' scientific skills in making briquettes from corncob waste and coffee grounds. The issue of low utilization of agricultural waste and lack of integration of real context in chemistry learning. The method used was pre-experimental with a One-Shot Case Study design, involving three groups of students in class XI Industrial Chemical Engineering. The assessment focused on the six stages of guided inquiry, namely observation, formulating problems, making hypotheses, conducting experiments, analyzing data, and drawing conclusions. The results showed that student activity reached 90.3 while scientific skills showed excellent results, with scores between 83-91.7. This is a novelty with the application of guided inquiry-based worksheets in a real context, namely the processing of organic waste into briquettes, which has not been widely explored in chemistry learning. This finding shows that applying LKPD in making corn stover and coffee grounds briquettes with a guided inquiry learning model is proven effective in developing students' scientific skills.